Hubungan Pola Asuh Orang Tua dengan Kejadian Temper Tantrum Anak Usia Prasekolah (3-6 Tahun) di Taman Kanak-Kanak - Ismi Adisti; Riska Amalya Nasution; Retty Okti Syafrini (JURNAL KEPERAWATAN RAFLESIA, 2022)
Temper tantrums are conditions where children experience unplanned outbursts of emotion and frustration. Children's emotional development will be disrupted if temper tantrums are not handled and left unchecked. One of the factors that can influence is parenting style. The research objective was to determine the relationship between parenting style and the incidence of temper tantrums. The research design is descriptive quantitative with a cross-sectional approach, the number of samples is 78 respondents with the Consecutive Sampling method. Data collection used the short version of the Parenting Style and Dimensions Questionnarie (PSDQ) instrument. Data were analyzed with univariate and bivariate analysis. Bivariate analysis using the tau control test. Statistical test results showed that there was a significant relationship between parenting style and temper tantrums (p<0.05), there was no authoritarian parenting relationship (p>0.05), there was no relationship with permissive parenting (p>0.05, there was no democratic relationship (p >0.05), and there was no relationship between indifferent parenting (p>0.05).There is a need for health promotion efforts regarding proper parenting.